Penguatan Aparatur Sekretariat DPRD dalam Perspektif Institusionalisme: Integrasi Old Institutionalism, New Institutionalism, dan Teori Tiga Pilar Kelembagaan - Panca Tuah Tuha; Maulan Aklil; Mat Amin; Fithriawan Nugroho; Jumadi Wal’ajro (Universitas 17 Agustus 1945 Semarang, 2026)
The strengthening of the Secretariat apparatus of the Regional Representative Council (DPRD) is a strategic issue in the governance of legislative administration at the regional level in Indonesia. However, studies on the DPRD Secretariat remain relatively limited and tend to emphasize structural and regulatory aspects, without comprehensively addressing institutional dynamics. This study aims to strengthen the DPRD Secretariat apparatus through an institutionalist perspective, using the Institutional Three Pillars Theory framework proposed by W. Richard Scott. This study is a conceptual paper developed through a narrative literature review approach, examining both classical and contemporary literature in the fields of institutionalism and public administration. The analysis focuses on how the regulatory, normative, and cognitive pillars interact to shape the institutional practices of the DPRD Secretariat as an institution supporting the legislative, budgeting, and oversight functions at the regional level. The study's findings show that the strengthening of the DPRD Secretariat apparatus cannot be understood solely as a consequence of formal regulation, but rather as an institutional process involving a balance between legal rules, professional values and norms, and collective meaning-making regarding the role and institutional identity. This study is not intended to empirically assess performance but offers a conceptual framework that can be used to understand the dynamics of regional legislative administration more holistically. Theoretically, this research contributes to enriching institutionalism studies in public administration by positioning the DPRD Secretariat as a complex and contextual institution. The conceptual framework offered is expected to serve as a reference for future empirical research and conceptual reflection for strengthening legislative administration institutions in Indonesia.